Toponimi Pada Nama Desa di Kabupaten Mojokerto: Kajian Etnolinguistik - Yuwafa Faurelio Yahya; Dania Kusuma Wardani; Nur Kholida Hanum; Taswirul Afkar (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Language cannot be separated from human life, humans who act as a role in the formation of civilization produce a masterpiece called culture and local wisdom. This study examines the relationship between the two which is related to the linguistics group. In linguistic studies, there is an approach, namely ethnolinguistics which is used to examine the relationship between language and community culture which produces various meanings of language. Through this approach, the study aims to describe the form of lexicon and toponymy of village names in Mojokerto Regency. This study uses a qualitative descriptive method with a note-taking technique. The data source used in this study is a book entitled